Triangle Analysis: Carbon Emissions, Economic Growth, And Poverty In Indonesia - Suryanto, Suryanto; Radhianita, Apriana; Juwita, Aulia Hapsari (Universitas Negeri Semarang, 2019)
This research tried to investigate the correlation between carbon emissions on poverty levels and the economic growth effect toward the level of poverty. This study utilizes secondary data-set time series from 2010 to 2016 across 34 provinces in Indonesia. The source of the data is from the Central Statistics Agency (BPS) and German watch. The data estimation uses a panel regression by Fixed Effect Model and processed using E-views software version 8.0. The results of the study reveal that 1) effect of carbon emission is positive but not significant on poverty levels; 2) economic growth affects the poverty level positively significant. Thus, the economic development that results in pollution (i.e., industrialization, transportation) should more controlled and in line with sustainable development goals (SDGs). Therefore, there are needs for the government to put effort into designing and making policies related to decreasing emissions. Furthermore, the government should also involve all stakeholders to participate in contributing to economic-environmental friendly. They have to increase their awareness in carrying out the policies set by the government and paying more attention to the waste screening process.